MODEL COMMUNITY GOVERNANCE DALAM PENYELENGGARAAN PEMERINTAHAN DESA - Rahmawati, Rahmawati (STIA SATYA NEGARA PALEMBANG, 2022)
The enactment of Law Number 6 of 2014 concerning Villages has brought fresh air to accelerate the development of villages and rural areas, where one of the fundamental changes is the recognition (recognition) of the function of the village as a Self Governing Community in line with local self government. The village law becomes the legal umbrella for the administration of village government, which at a certain level opens up space for more autonomous governance for the government at the village level. Governance includes all the mechanisms, processes, and institutions through which citizens and community groups express their interests, exercise legal rights, fulfill obligations and bridge differences between them. This type of research is descriptive research with a qualitative approach. This approach and type is used because the researcher wants to explain and describe Community Governance in village government. The conclusion from this article is that one model of community governance is village government, where in the village government the center of local political power is represented through the Village Head, Village Consultative Body, and their apparatus. The position of village government is also very important considering that the majority of Indonesia's population lives in rural areas. The implementation of village government in the Village Law cannot be separated from the participation of the village community. Keywords: Community Governance, Village Government